Anti-site mixing and magnetic properties of Fe3Co3Nb2 studied via neutron powder diffraction. (30th November 2016) - Xu, Xiaoshan; Zhang, Xiaozhe; Yin, Yuewei; Balasubramanian, Balamurugan; Das, Bhaskar; Liu, Yaohua; Huq, Ashfia; Sellmyer, David J
Abstract: We studied the crystal structure and magnetic properties of the rare-earth-free intermetallic compound Fe3 Co3 Nb2, which has recently been demonstrated to have potentially high magnetic anisotropy, using temperature-dependent neutron powder diffraction. The temperature dependence of the diffraction spectra reveals a magnetic transition between 300 and 400 K, in agreement with the magnetometry measurements. According to the structural refinement of the paramagnetic state and the substantial magnetic contribution to the diffuse scattering in the ferromagnetic state, the Fe/Co anti-site mixing is so strong that the site occupation for Fe and Co is almost random. The projection of the magnetic moments turned out to be non-zero along the c axis and in the a–b plane of Fe3 Co3 Nb2, most likely because of the exchange interactions between the randomly orientated nanograins in the samples. These findings suggest that future studies on the magnetism of Fe3 Co3 Nb2 need to take the Fe/Co anti-site mixing into account, and the exchange interactions need to be suppressed to obtain large remanence and coercivity.